9-7y-6-7y=5

Subtract 6 from 9.

-7y+3-7y=5

Subtract 7y from -7y.

-14y+3=5

-14y+3=5

Subtract 3 from both sides of the equation.

-14y=5-3

Subtract 3 from 5.

-14y=2

-14y=2

Divide each term in -14y=2 by -14.

-14y-14=2-14

Cancel the common factor of -14.

Cancel the common factor.

-14y-14=2-14

Divide y by 1.

y=2-14

y=2-14

Simplify 2-14.

Cancel the common factor of 2 and -14.

Factor 2 out of 2.

y=2(1)-14

Cancel the common factors.

Factor 2 out of -14.

y=2⋅12⋅-7

Cancel the common factor.

y=2⋅12⋅-7

Rewrite the expression.

y=1-7

y=1-7

y=1-7

Move the negative in front of the fraction.

y=-17

y=-17

y=-17

The result can be shown in multiple forms.

Exact Form:

y=-17

Decimal Form:

y=-0.142857‾

Solve for y 9-7y-6-7y=5